PENGARUH PERTUMBUHAN EKONOMI DAN ANGKA KEMISKINAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI SUMATERA SELATAN TAHUN 2010-2018 - Andri Irawan (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
This study aims to determine the effect of economic growth (x1), and poverty rate (x2), on human development index (y) in South Sumatera in 2010-2018. The data used is secondary data from Central Bureau of Statistics.The method of analysis used is panel data regression. The results show that all independent variables simultaneously affect dependet variable proven by the f-statistic value smaller than α 5%. The result of t-test shows that economic growth (x1) has negatively and significantly effect on human development index (y), while poverty rate (x2) has negatively and significantly effect on human development index (y). The result of coefficient of determination test shows that dependent variable can be explained by independent variable amounted up to 89,3% and the rest of 10,7% is explained by other factors outside this model.